EVALUASI BANGUNAN ASRAMA MAHASISWA BULAKSUMUR RESIDENCE UGM BERDASARKAN GREENSHIP EXISTING BUILDING PADA ASPEK ENERGY EFFICIENCY AND CONSERVATION - , AHMAD FAQIH MAHALLI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Buildings are one of the largest energy consumers, which are 70% from the total electric consumption in Indonesia, and uses 50% of the total energy use in Indonesia. Therefore, green concept in buildings will be developed in order to create a building that saves more energy, yet is still comfortable to the occupants. Green building certification in Indonesia is held by the Green Building Council Indonesia (GBCI). This research discusses about the evaluation of Bulaksumur Residence dormitory building based on Greenship Existing Building in Energy Efficiency and Conservation aspects. There are several parameters that could not be tested because the data were unavailable. Energy Use Intensity (EUI) of Bulaksumur Residence is too low, that is 8.78 â 9.36 kWh/m2.year. The low value of EUI may be caused by several live pattern scenarios. These scenarios are the air conditioning system that is not available, the rules, the using of energy saving lamp, and the academic schedule. Because of the air conditioning system that is not available, the electrical consumption loads will be used for lighting and other electronic devices. Lighting wattage of the occupantâs rooms are 1.69 watt/m2. And the illumination of the room is 155 lux. The illumination value is below standard value, which is 250 lux. Although there is no air conditioning system and a small value of illumination, the occupants will still feel comfortable with the building condition. The low value of EUI shows that Bulaksumur Residence dormitory has done energy saving. This can be emulated in development of another dormitory.